Kegiatan Ice Breaking Sebagai Konsentrasi Pelatihan Diklat Satpam Di Sukoharjo - Agatha Cahya Kusuma Wardani; Tiara Fadhilah Hasna Fadholi; Anniez Rachmawati Musslifah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Security Guard Training and Training in Sukoharjo faces challenges in increasing the effectiveness of learning and concentration of participants. The activity "Ice Breaking as a Concentration for Security Guard Training Training in Sukoharjo" is proposed as an innovative approach to start training in a fresh and fun atmosphere with the aim of providing a brief overview of the importance of ice breaking in the context of security guard training in Sukoharjo as an effort to achieve optimal learning effectiveness. Ice breaking is seen as an essential first step to build relationships between participants, create a comfortable atmosphere, and increase participant motivation. The method for this service is in 3 stages starting from opening, content and closing and the population is security guards in Sukoharjo. The conclusion is that the implementation of ice breaking in security guard training in Sukoharjo is not just an opening step, but is a critical element in achieving training objectives by providing a strong foundation for effective and continuous learning.